2002
DOI: 10.1097/00005392-200211000-00088
|View full text |Cite
|
Sign up to set email alerts
|

Symphysiotomy: A Viable Approach for Delayed Management of Posterior Urethral Injuries in Children

Abstract: Symphysiotomy is hereby revisited as a simple and effective approach for repairing traumatic posterior urethral injuries in the pediatric population. It can be performed instead of transpubic urethroplasty to manage long or otherwise complicated strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…At surgical reconstruction through longitudinal abdominal approach, the bladder and vagina were exposed extraperitoneally with separation of symphysis pubis to confirm previous findings 2 . Muscular tissue of the urethral sphincter was not identified.…”
Section: Case Reportmentioning
confidence: 63%
“…At surgical reconstruction through longitudinal abdominal approach, the bladder and vagina were exposed extraperitoneally with separation of symphysis pubis to confirm previous findings 2 . Muscular tissue of the urethral sphincter was not identified.…”
Section: Case Reportmentioning
confidence: 63%
“…Das et al [15] operated on 10 children using transpubic approach with 100% success rate. Basiri et al [16] reported symphysiotomy in 10 children (both boys and girls); all were successful and continent without any complications. Podesta and Podesta [17] did a comparative study of perineal vs transpubic urethroplasty for traumatic posterior urethral distraction defect in children and found a stricture-free rate of 84% for the perineal approach and 100% in those who underwent transpubic urethroplasty.…”
Section: Discussionmentioning
confidence: 98%
“…Of the 23 patients with incontinence after delayed urethral repair, four patients (17%) had nocturnal incontinence alone [33,35]. In two of 23 cases (9%), SUI resolved spontaneously at 4 weeks and 6 months, respectively [36,38]. Two of 23 patients (9%) were managed with selfintermittent catheterization for incontinence [33,39].…”
Section: All Patients Undergoing Delayed Repair Required Either An Abmentioning
confidence: 99%
“…Five of 23 patients (22%) underwent surgery for SUI with either an artificial urinary sphincter or fascial sling [4,40,41]. Ten of 23 patients (43%) had persistent SUI at a follow-ups ranging from 4 months to 6 years [3,14,[37][38][39].…”
Section: All Patients Undergoing Delayed Repair Required Either An Abmentioning
confidence: 99%